The Queensland Virtual Integrated Practice (VIP) partnership program pilot study: an Australian-first model of care to support rural general practice - Breanna Lepre; Jennifer Job; Zena Martin; Natalie Kerrigan; Claire Jackson (BMC, 2023)
Abstract Background There is a critical lack of medical workforce internationally, and this is particularly notable in rural and remote Australia where strategies to address workforce shortages are urgently required. This pilot study aimed to implement and evaluate a Virtual Integrated Practice (VIP) Program in the Australian rural primary care setting. Methods The VIP model was developed using co-creation methodology and involves an urban GP joining a rural general practice team to provide ongoing care to patients remotely via secure telehealth. The pilot study was conducted in two western Queensland general practices, commencing in October 2021 with one rural practice and extending to an additional rural practice from November 2022. Evaluation included a retrospective review of service, billing and cost data, and an online survey for patients. Ethical approval was obtained from the University of Queensland Human Research Ethics Committee (Project number: 2021/HE002434). Results There were 1468 services provided through to December 2022, including general consults (n = 1197), therapeutic procedures (n = 68), mental health treatment plans (n = 68) and chronic disease management plans (n = 59). Patients were predominantly female (73.1%) and did not have their appointment at the practice (57.8%). Among 1282 occasions of service, less than 20% of consultations (n = 224) required support from staff (e.g., a nurse), and more than half were repeat patient encounters (53.0%). Survey respondents (n = 45) indicated that they were satisfied (9.3%) or highly satisfied (90.7%) with the care provided, and importantly, 95.5% of respondents reported that the service improved their access to the GP. More than 20% of respondents indicated that they would attend the Emergency Department if virtual care was not available. Conclusions Data from this pilot study has informed translation to an additional 20 vulnerable rural general practices in three further rural regions in Queensland in 2023 and evaluation is ongoing. This pilot study demonstrates the feasibility and acceptability of an innovative, digitally supported community-focussed, healthcare initiative to arrest the decline in rural general practice workforce, improve patient care access and support rural practice viability.